Diseases of Blood - C. K. Vishnu Priya; Mutum Sangeeta Devi; B. Niveditha; Athokpam Poireiton; Ch. Anupriya; Ravi Ranjan; . Poorni; DKS Lakshminrusimhan (Diseases of Blood, 2022)
RBCs contain hemoglobin, the oxygen-transporting protein. Hemoglobin releases carbon dioxide and picks up oxygen in the lungs. The heart then pumps this oxygen-rich blood through arteries that branch into smaller arteries until they reach the capillaries (tiny vessels that connect the arterial and venous systems). Blood disorders can affect any of the three main components of blood: Red blood cells, which carry oxygen to the body’s tissues White blood cells, which fight infections Platelets, which help blood to clot The diseases of the blood affects both hard and soft tissues of the oral cavity. The common oral manifestations of hematologic conditions of white blood cells includes cyclic hematopoiesis (cyclic neutropenia), leukemias, lymphomas, plasma cell dyscrasias, and mast cell disorders. Red blood cell disorders includes anemias, and less common red blood cell dyscrasias (sickle cell disease, hemochromatosis, and congenital erythropoietic porphyria) as well as thrombocytopenia. History and clinical examination is important in evaluating the patients with haematological disorder and Proper diagnosis is important to initiate the treatment.